Nitrogen-fixing symbiosis induces differential accumulation of Medicago truncatula leaf defence metabolites in response to pea aphid infestation - Benjamin, Goodluck; Pacoud, Marie; Boutet, Stéphanie; Clement, Gilles; Brouquisse, Renaud; Gatti, Jean-Luc; Poirié, Marylène; Frendo, Pierre (Frontiers in Plant Science, 2025)
Legume symbiosis with rhizobial nitrogen-fixing bacteria enables legumes to grow in nitrate-depleted soils. Rhizobial symbioses also induce systemic plant defence against bioaggressors. We investigated how nitrogen-fixing symbiosis (NFS) in the legume Medicago truncatula can prime plant defence against the pea aphid Acyrthosiphon pisum. We analysed metabolite modification using both gas chromatography/mass spectrometry (GC-MS) and liquid chromatography/mass spectrometry (LC-MS) and defence pathway gene expression using qPCR in the leaves of both NFS and nitrate-fed [non-inoculated (NI)] plants after aphid infestation (Amp). The accumulation of primary and secondary metabolites was modulated by both NFS and aphid infestation. Sixty-two defence-related metabolites, such as salicylate, pipecolate, gentisic acid, and several soluble sugars, were differentially regulated by aphid infestation under both NFS and NI conditions. Nineteen metabolites, including triterpenoid saponins, accumulated specifically under NFS_Amp conditions. Gene expression analysis showed that aphid-infested plants exhibited significantly higher expression of chalcone isomerase, flavonol synthase, hydroxyisoflavone-O-methyl transferase, and pterocarpan synthase, while D-pinitol dehydrogenase was only significantly induced in NI-infested leaves. Our data suggest that NFS, in addition to being a plant nitrogen provider, stimulates specific legume defences upon pest attack and should also be considered a potential tool in Integrated Pest Management strategies.